2012
DOI: 10.1038/bjc.2012.74
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial D310 mutations in the early development of breast cancer

Abstract: Background:The role of mitochondrial DNA (mtDNA) mutations in the development of breast cancer is largely unknown. In this study, we investigated the frequency and pattern of mutations in the D310 region, the most commonly mutated region in mtDNA, in a series of breast lesions.Methods:Using capillary electrophoresis, we genotyped the D310 sequence of neoplastic epithelial cells from 23 patients with synchronous ductal carcinoma in situ (DCIS) and invasive ductal carcinoma (IDC), 26 patients with IDC only and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…Sauter and colleagues detected mtDNA mutations in primary breast tumor and matched breast NAF [100]. Similarly, other studies have shown a correlation between mtDNA mutations in breast tumor tissues and in biological fluids including serum [81, 95, 99, 127, 137]. However, in some studies, mtDNA mutations were undetectable or follow-up was not available [134], therefore, further studies with more advanced techniques and long-term follow-up are necessary to robustly establish whether mtDNA mutations in blood, NAF, or other biological fluids could be used for early detection of breast cancer.…”
Section: Somatic Mtdna Mutations and Risk For Breast Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…Sauter and colleagues detected mtDNA mutations in primary breast tumor and matched breast NAF [100]. Similarly, other studies have shown a correlation between mtDNA mutations in breast tumor tissues and in biological fluids including serum [81, 95, 99, 127, 137]. However, in some studies, mtDNA mutations were undetectable or follow-up was not available [134], therefore, further studies with more advanced techniques and long-term follow-up are necessary to robustly establish whether mtDNA mutations in blood, NAF, or other biological fluids could be used for early detection of breast cancer.…”
Section: Somatic Mtdna Mutations and Risk For Breast Cancermentioning
confidence: 97%
“…Mutations in nDNA such as those in p53 , BRCA-1 and BRCA-2 , PTEN , CHEK2 , ATM (ataxia telangiectasia mutated), XPD (xeroderma pigmentosum group D)/ERCC2 (excision repair cross-complementing rodent repair deficiency, complementation group 2 protein), and HER-2 (human epidermal growth factor receptor) have been extensively studied in breast cancer [24, 74], whereas mtDNA mutations are only now becoming recognized as an important aspect of breast cancer development and resistance to apoptosis. Studies performed in the last few years have characterized various alterations in mtDNA in breast cancer, including point mutations, mtDNA polymorphisms, mtDNA depletion, microsatellite instability, insertions, changes in mtDNA copy number, homoplasmy, and heteroplasmy of mtDNA [18, 33, 51, 68, 69, 7599]. Breast nipple aspirate fluid (NAF) with mtDNA mutations at position 204, 207, and 16293 has been suggested to be indicative of breast cancer and mtDNA D-loop mutation has also been proposed as an independent prognostic marker for breast cancer [100, 101].…”
Section: Mitochondrial Dna Mutations In Breast Cancermentioning
confidence: 99%
“…The D-loop control region sites such as 309C>T, 310T>C and 16223C>T are observed in almost every stomach patient specimen analyzed as it demonstrates near confluence in this small cohort. The non-coding displacement (D)-loop, especially a mononucleotide repeat (poly-C) between 303 and 315 nucleotides (D310), has been recently identified as a frequent hotspot for mutations in human neoplastic, including stomach cancer [18]. As such, this unique attribute may be considered as a potential biomarker for stomach cancer provided this behavior is consistent in transforming to blood.…”
Section: Discussionmentioning
confidence: 99%
“…In 34% of rectal carcinomas (n = 38) and 38% of sigmoid carcinomas (n = 25), D310 sequence alterations could be detected [66]. In breast cancer patients, 68% of ductal carcinomas in situ (n = 23) and 71% of invasive ductal carcinomas (n = 26) harbor D310 sequence alterations [67]. In 11 of 18 breast cancers, mtDNA mutations could be detected, of which 42% are D310 alterations [68].…”
Section: Mtdna Displacement-loop Alterationsmentioning
confidence: 99%
“…D310 mutation detection could represent a potential early marker for premalignant human disease. Histologically normal breast epithelial cells, adjacent to invasive ductal carcinomas that carry D310 mutations, already display D310 alterations [67]. D310 alterations are also present in normalappearing (46%) and dysplastic (57%) gallbladder epithelia accompanying gallbladder carcinomas [69].…”
Section: Mtdna Displacement-loop Alterationsmentioning
confidence: 99%